Redesain Kursi Santai Lanjut Usia Dengan Pendekatan Quality Function Deployment (QFD) - Purwanto; Ezar Amrullah (JERA : Journal of Engineering Research and Application, 2025)
RAMAH Elderly Home is a social institution that functions to accommodate, care for and develop the elderly. Various kinds of facilities are provided in elderly homes, one of which is a lounge chair as a place for the elderly to relax when they have finished their activities or when they have no activities. The research procedure uses the QFD method using the HoQ (House of Quality) matrix. The HoQ matrix that is assessed is to determine the level of relationship between (Whats) and (How) where the determination of this relationship goes through a process and the final result is a house of quality matrix or House of Quality. The results of interviews with 26% of the population of elderly home residents complained of discomfort when using lounge chairs in RAMAH elderly homes. From the results of the Nordic Body Map (NBM) questionnaire given to elderly people who had complaints about their hips, 60% of the total sample felt quite sick, while 40% felt pain. In the left elbow and right elbow, 60% of the total sample felt quite pain, while the other 40% did not feel pain. The results of preparing the HOQ matrix show that the highest level of importance will be the main priority as a basis for product design and development. The highest level of importance is the backrest and seat material with each weight (5.00), seat length with weight (4.97), ideal seat height with weight (4.64), no sharp and sturdy sides and corners with each weight (3.97), and the lowest is the footrest with weight (2.97).